Demographic change and regional labour markets: the case of Eastern Germany - Beate Henschel; Carsten Pohl; Marcel Thum (Center for Economic Studies and ifo Institute (CESifo), 2008)
Demographic change will be one of the most challenging issues for industrialized economies in the decades to come. In this paper, we focus on the impact of demographic change on labour markets. By setting up a stylized model of a regional labour market, we are able to analyze the interaction of labour demand and supply during demographic transitions. The simulation results for eastern Germany, a forerunner in the demographic process, show that the population decline will not help to reduce the currently high unemployment among the low-skilled dramatically. Among the high-skilled, scarcities will play a major role and could impede the development of industrial centers.
Keywords: J1; J2; R1; 330; demographic change; labour market; unemployment; long-run projection; general equilibrium; Regionaler Arbeitsmarkt; Alternde Bevölkerung; Regionale Arbeitslosigkeit; Arbeitsmarktprognose; Allgemeines Gleichgewicht; Neue Bundesländer